Kontribusi Pendapatan Pertanian Tembakau terhadap Pendapatan Rumah Tangga Petani Padi di Desa Sumberharjo - Moh Zidan Artefa; Darsan Darsan; Fina Sulistiya Ningsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Tobacco is a leading commodity in Sumberharjo Village because it has high economic value, thereby improving the financial welfare of farming families. Farmers' families derive their income from various activities, including tobacco cultivation in Sumberharjo Village. This study was conducted to determine the contribution of income from tobacco farming to the total income of farmers. This study was conducted in November and December 2024 in Sumberharjo Village. The study included 40 respondents, selected using simple random sampling. The variables in this study included farmers' income, revenue, and farming costs, such as taxes, depreciation costs, seeds, fertilizers, agricultural chemicals, and labor costs. This study used farming analysis, including an analysis of total costs incurred by farmers, an analysis of income using the calculation of total production multiplied by the selling price, an analysis of farmers' income using the calculation of total income minus total costs, and an analysis of the contribution of tobacco farming income to total farmer income. The analysis results indicate that tobacco farming income makes a significant contribution to total farmer income. Therefore, farmers are encouraged to develop tobacco farming to achieve higher income.